RTK GPS Performance Assessment for Long Baseline Deformation Monitoring - Mohd Zuber, Muhammad Azfar (Universiti Teknologi PETRONAS, 2013)
An offshore platform or correctly is a large structure with facilities to drill wells, to extract and process oil and natural gas, and to temporarily store product until it can be brought to shore for refining and marketing. For a normal GPS, after we obtained the coordinates of certain point, we have to process them and this will take time. For RTK GPS, it is real time process. It means that the data obtained can be processed on time and this can reduce time and occupation load. When a platform is hit by external forces, it will move a little bit from its original position, maybe just about 10cm. How can we measure the movement of the platform at the middle of the sea? This project work will be using the knowledge that author had learnt during the period of study. It is a method to test for the practicality of the knowledge that had been learned. In conducting this project, the author has to study about RTK GPS performance, understand the concept and the functions of RTK GPS. Next, some tests are going to be conducted, which is distance, accuracy, precision, and performance of RTK GPS single-based test.